Cardinal revealed preference, price-dependent utility, and consistent binary choice - Victor H. Aguiar; Roberto Serrano (Brown University, Department of Economics, 2018)
We present a new notion of cardinal revealed preference that exploits the expenditure information in classical consumer theory environments with finite data. We propose a new behavioral axiom, Acyclic Enticement (AE), that requires the acyclicity of the cardinal revealed-preference relation. AE is logically independent from the Weak Axiom of Revealed Preference (WARP). We show that the Generalized Axiom of Revealed Preference (GARP), which characterizes the standard rational consumer, is logically equivalent to AE and WARP. We propose a new notion of rationalization by means of a price-dependent utility function that characterizes AE, which in particular is suitable for welfare analysis. We also propose a consistency condition for preference functions that is equivalent to WARP. We use our axiomatic decomposition to show, in experimental and scanner consumer-panel data sets, that AE explains the majority of the predictive success of GARP. Moreover, AE taken alone is superior in predictive success to both WARP and GARP.
Keywords: C60; D10; 330; consumer theory; rationality; revealed preference approach; bounded rationality